1987
DOI: 10.1007/bf00014527
|View full text |Cite
|
Sign up to set email alerts
|

Redescription and assignment of Alona globulosa Daday, 1898 to a new genus Notoalona and a description of Notoalona freyi sp. nov.

Abstract: The species Daday (1898) describes as Alona globulosa has been critically studied, based on many populations from tropical and subtropical regions of the world, over its whole geographical range . A new species and a new subspecies are described . Based on the morphological characters of this species group, which are markedly different from those of the genera previously used for this species, namely Alona, Alonella,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…12F-J). Described from Sri Lanka (Daday, 1898) as Alona, then moved to Indialona by Smirnov (1971) and later to Notoalona (Rajapaksa and Fernando, 1987c). The latter authors concluded that N. globulosa occurs also in the tropical part of the New World, and subsequently similar populations were also found in Southern Mexico (Elías-Gutiérrrez et al, 2006, 2008.…”
Section: Notoalona Rajapaksa and Fernando 1987mentioning
confidence: 99%
“…12F-J). Described from Sri Lanka (Daday, 1898) as Alona, then moved to Indialona by Smirnov (1971) and later to Notoalona (Rajapaksa and Fernando, 1987c). The latter authors concluded that N. globulosa occurs also in the tropical part of the New World, and subsequently similar populations were also found in Southern Mexico (Elías-Gutiérrrez et al, 2006, 2008.…”
Section: Notoalona Rajapaksa and Fernando 1987mentioning
confidence: 99%
“…Littoral, associated with vegetation. For a detailed description see Rajapaksa and Fernando (1987c). Distributed in Africa and tropical Asia, yet forms a species complex .…”
Section: As L Acuticostata]mentioning
confidence: 99%
“…The organisms were identified using the following specialized literature: Bergamin, 1932;Edmondson, 1959;Scourfield & Harding, 1966;Smirnov, 1974Smirnov, , 1996Young, 1998;Elmoor-Loureiro, 1997;Paggi, 1972;Duigan, 1992;Dumont & SilvaBriano, 1998;Rajapaksa & Fernando, 1987a;Duigan & Murray, 1987;Rajapaksa & Fernando, 1987b;Paggi, 1980;Smirnov, 1998;Frey, 1982;Alonso, 1987;Pennak, 1989;Olesen, 1996;Biraben, 1939;Olivier, 1962;Smirnov & Timms, 1983; Sinev1999. Table 1 shows the results obtained for the physical and chemical variables analysed.…”
Section: Quantitative and Qualitative Analyses Of The Family Chydoridaementioning
confidence: 99%